The isolation of pentose-assimilating yeasts and their xylose fermentation potential - Martins, Gisele Marta [UNESP]; Bocchini-Martins, Daniela Alonso [UNESP]; Bezzerra-Bussoli, Carolina [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Boscolo, Maurício [UNESP]; Monteiro, Diego Alves [UNESP]; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP] (Springer Nature, 2018)
For the implementation of cellulosic ethanol technology, the maximum use of lignocellulosic materials is important to increase efficiency and to reduce costs. In this context, appropriate use of the pentose released by hemicellulose hydrolysis could improve de economic viability of this process. Since the Saccharomyces cerevisiae is unable to ferment the pentose, the search for pentose-fermenting microorganisms could be an alternative. In this work, the isolation of yeast strains from decaying vegetal materials, flowers, fruits and insects and their application for assimilation and alcoholic fermentation of xylose were carried out. From a total of 30 isolated strains, 12 were able to assimilate 30 g L−1 of xylose in 120 h. The strain Candida tropicalis S4 produced 6 g L−1 of ethanol from 56 g L−1 of xylose, while the strain C. tropicalis E2 produced 22 g L−1 of xylitol. The strains Candida oleophila G10.1 and Metschnikowia koreensis G18 consumed significant amount of xylose in aerobic cultivation releasing non-identified metabolites. The different materials in environment were source for pentose-assimilating yeast with variable metabolic profile.
Keywords: Ethanol; Xylose; Yeasts